Number in the world's languages a comparative handbook - Acquaviva, Paolo, 1967-; Daniel, Michael (Comparative handbooks of linguistics ;, 2022)
The strong development in research on grammatical number in recent years has created a need for a unified perspective. The different frameworks, the ramifications of the theoretical questions, and the diversity of phenomena across typological systems, make this a significant challenge. This book addresses the challenge with a series of in-depth analyses of number across a typologically diverse sample, unified by a common set of descriptive and analytic questions from a semantic, morphological, syntactic, and discourse perspective. Each case study is devoted to a single language, or in a few cases to a language group. They are written by specialists who can rely on first-hand data or on material of difficult access, and can place the phenomena in the context of the respective system. The studies are preceded and concluded by critical overviews which frame the discussion and identify the main results and open questions. With specialist chapters breaking new ground, this book will help number specialists relate their results to other theoretical and empirical domains, and it will provide a reliable guide to all linguists and other researchers interested in number.